Infections With Stenotrophomonas maltophilia in Children Undergoing Anticancer Therapy or Hematopoietic Cell Transplantation: A Multicenter Nationwide Study. Issue 10 (8th July 2022) - Richert-Przygonska, Monika; Czyzewski, Krzysztof; Dziedzic, Magdalena; Zalas-Wiecek, Patrycja; Gryniewicz-Kwiatkowska, Olga; Gietka, Agnieszka; Malas, Zofia; Semczuk, Katarzyna; Chelmecka, Liliana; Zak, Iwona; Salamonowicz-Bodzioch, Malgorzata; Fraczkiewicz, Jowita; et al.
Abstract : Background: Infections caused by Stenotrophomonas maltophilia (SM) have documented high mortality rate in immunocompromised patients. Aim: This nationwide multicenter study was performed to analyze the epidemiology of SM infections in children undergoing anticancer therapy (pediatric hematology and oncology [PHO]) or hematopoietic cell transplantation (HCT) over 2012–2019, including incidence and outcome of SM infections, as well as treatment regimens and multidrug resistance. Methods: Cumulative incidence of SM infections was calculated using the competing risk analysis from the day of diagnosis (PHO setting) or from the day of transplantation (HCT setting). The Kaplan-Meier method was used to determine survival from infection. Results: During the study period of 8 years, a total number of 1356 HCTs and 7337 children newly diagnosed for malignancy were analyzed. Diagnosis of acute leukemia was a predisposing factor for SM infection. The cumulative incidence of SM infections was comparable in HCT patients in comparison to PHO (0.81% vs. 0.76%). High rate of trimethoprim/sulfamethoxazole susceptibility among SM isolates was observed in both groups of patients (80.8%). Although this was the drug of choice, survival rates from SM infections were significantly lower in HCT than in PHO (45% vs. 85%, P = 0.001, log-rank test). We found the transplant procedure and lack of clinical resolution after 18 days of antibiotic therapy to be independent mortality risk factors. Conclusions: The risk of SM infections and the occurrence of resistant bacterial strains in allo-HCT patients were comparable to PHO patients. Irrespective of target antibiotic therapy, the outcome of SM infections was better in the PHO setting.